CB₁ Reverse Agonists: A Cheminformatic and Patent Landscape Study - Deepak Sharma (International Journal of Cheminformatics, 2025)
The endocannabinoid system plays a crucial role in numerous physiological functions, making cannabinoid receptor 1 (CB1) an attractive target for therapeutic development. This review provides a systematic analysis of patent filings from 2019 to 2023 that focus on small-molecule CB1 reverse agonists. It begins with an overview of the endocannabinoid system, highlighting CB1’s involvement in energy balance, pain regulation, and neuroinflammatory processes The main section of the review examines fifteen patents covering diverse structural classes—such as pyrazoles, triazoles, and piperidines—designed to achieve high CB1 affinity and efficacy. Evaluation of these patents uncovers innovative scaffolds aimed at enhancing receptor selectivity, limiting central nervous system penetration, and improving pharmacokinetic characteristics. Many of the patented compounds target metabolic disorders, including obesity and type 2 diabetes, by modulating CB1 signaling in peripheral tissues. Other therapeutic areas addressed include chronic pain, neurodegenerative conditions, and substance use disorders. Each patent is analyzed for its inventive aspects, synthetic feasibility, and reported in vitro and in vivo results Insights from industry expert interviews underscore ongoing challenges, such as maintaining a favorable safety profile, preventing neuropsychiatric side effects, and addressing formulation difficulties. The review concludes by highlighting emerging trends and suggesting future directions for CB1 reverse agonist development. Recommendations include using structure–activity relationship studies to fine-tune central versus peripheral activity, applying advanced drug-delivery approaches, and incorporating biomarker-driven clinical strategies. By integrating recent patent data and expert perspectives, this review seeks to guide medicinal chemists and pharmacologists in advancing CB1-focused drug discovery.
Keywords: CB1 antagonism; CB1 receptor; Cannabinoid signaling pathway; metabolic disease management; patent filings; pharmacological reverse agonists